Polskie wątki kommemoratywne w ukraińskiej polityce pamięci – na przykładzie nazw ulic miast obwodowych Galicji Wschodniej po 1991 roku - Szczepański, Jan; Szczepańska, Marta (Przegląd Wschodnioeuropejski, 2024)
This article presents Polish naming threads among the streets of the largest cities in Eastern Galicia – Lviv, Ivano-Frankivsk and Ternopil after 1991. Before World War II these were Polish voivodeship cities, culturally dominated by Poles and Jews. Nowadays they are dominated by Ukrainians, who for the last 30 years have been trying to form their ambiguous historical policy. The politics of memory in these cities are conducted in two ways – on the one hand, they are shaping the symbolic landscape based on commemorating figures, organisations, dates or incidents related to Ukrainian nation-building processes, and on the other hand, they are returning to the multicultural heritage. A relevant thread are the names of streets and squares commemorating persons and organisations connected with Polish culture, which are still functioning and their number is increasing. The text indicates the reasons for this phenomenon, as well as the social and political implications arising from it.